Spray Pyrolysis-Derived Cobalt Oxide Thin Films: Synthesis and Optical Property Evaluation - Ghimire, Muskan; Karki, Bishow; Pradhan Joshi, Leela; Kandel, Lekhanath; Kandel, Mani Ram; Pradhan, Sharmila (Amrit Journal, 2025)
This study presents a simple and cost-effective approach for synthesizing cobalt oxide (Co3O4) thin films on glass substrates using a homemade spray pyrolysis technique. The investigation centers on how thermal treatment affects the optical properties and band gap of Co3O4 thin films, synthesized with varying precursor concentrations and layer thicknesses. As-synthesized Co3O4 thin films stand out for its remarkable catalytic activity, thermal stability, and optical characteristics attributed to variable oxidation states of Co, strong Co-O bonds, and a narrow band gap. X-ray diffraction (XRD) analysis confirmed the formation of crystalline Co3O4, with crystallite size increasing from 12.52 nm (non-annealed) to 16.23 nm after annealing. Optical transmittance data were used to determine the band gap energies, revealing that non-annealed films possessed higher band gap values. This indicates a consistent decrease in band gap energy with increasing annealing temperature. Overall, the spray pyrolysis method offers practical advantages for thin film fabrication, including operational simplicity, scalability, and low production cost.